INCREASING STUDENTS’ VOCABULARY ON IRREGULAR VERBS BY USING CROSSWORD PUZZLE - Sentya Montoali; Maikel Sanger; Sarah Kamagi (Program Studi Pendidikan Bahasa Inggris, 2023)
This study looks into the use of crossword puzzles to help pupils build their vocabulary. The research subject for this study was decided upon in class VII b at SMP Negeri 3 Tondano. There are 20 students in this class. The pre-experimental design of this study included pre- and post-tests for a single group. Scores from the pre- and post-tests following therapy were used to collect the data. The minimum and maximum scores in this investigation were 50 and 90, respectively. The results showed that the pre-test mean score was 63 and the post-test mean score was 78.5. It indicates that the post-test result is better than the pre-test. As a result, it can be said that teaching vocabulary using crossword puzzles differs significantly from other methods. Thus, it can be said that crossword puzzles can help pupils in SMP Negeri 3 Tondano's seventh grade increase their vocabulary. This demonstrates how crossword puzzles can be used by English teachers to expand their pupils' vocabulary.